Chronic kidney damage in the adult Fontan population. (15th April 2018) - Lee, D.; Levin, A.; Kiess, M.; Sexsmith, G.; Chakrabarti, S.; Barlow, A.; Human, D.; Grewal, J.
Abstract: Objectives: 1) To determine the accuracy of estimated GFR (eGFR) as compared to directly measured GFR (mGFR) in the adult Fontan population; 2) to determine the true prevalence of chronic kidney damage (CKD) as determined by uACR AND eGFR. Methods: Prospective study of 81 patients Fontan patients (≥ 18 years) followed at St. Paul's Hospital, University of British Columbia. CKD-EPI and MDRD equations used to calculate eGFR, mGFR determined by 99m Tc-DTPA renal dynamic imaging and urine albumin to creatinine ratios were calculated. Results: The mGFR was 93 ± 27 ml/min/1.73 m 2 : 28 (53%) had an mGFR < 90 ml/min/1.73 m 2 and 1 (2%) had an mGFR < 60 ml/min/1.73 m 2 . There was a modest correlation between mGFR and eGFR (EPI/MDRD) (r = 0.50, p < 0.0001 and r = 0.54, p < 0.0001 respectively). Both eGFR (EPI) (bias 27.0; 95% CI 18.0–27.7 ml/min/m 2, p < 0.0001) and eGFR (MDRD) (bias 15.5; 95% CI 7.6–17.4 ml/min/m 2, p < 0.0001) overestimated GFR as compared to mGFR. Among patients with an eGFR (EPI)/(MDRD) > 90 ml/min/1.73 m 2, 50% and 46% respectively had an mGFR < 90 ml/min/1.73 m 2 . Significant albuminuria (> 3 mg/mmol) was present in 33% and upwards of 32% of patients with a normal eGFR (MDRD/EPI) had evidence of CKD with uACR > 3 mg/mmol. Using combined criteria of eGFR < 90 ml/min/1.73 m 2 and/or uACR > 3 mg/mmol, 46% of patients had evidence of CKD. Conclusions: This study draws attention to the need for stringent CKD screening as an important proportion of CKD is currently not being detected. Mild undetected CKD, an early marker of end organ damage, may also be an early sign of Fontan failure that requires warrants further research.